Politics, ethics and emotions in 'New India' - Gudavarthy, Ajay (London Routledge, 2023)
How do emotions mobilise in politics? How do they frame ideologies? Broadly focusing on these questions, this book explains the role emotions play in Indian politics and the part they played in the aftermath of the 2019 general elections. It traces the consolidation of the Right in India and highlights the reasons for its electoral successes with a focus on the interplay between ethics and emotions such as fear, anxiety, guilt, shame, anger, hatred, betrayal, and violence. At the same time, it traces the changing dynamic in the way we think about politics and analyses the failure of liberal democratic institutions to make space for emotions in politics and political motivations. An accessible and essential guide to understanding contemporary India, this book will be of great interest to scholars and researchers of politics, especially governance and political theory, as well as South Asian studies.
Keywords: Governance Sector; Indian Politics; Governance and Political theory; Ethics of India